FIND THE ANSWERS

Convert 11-4x=(3x-2)^2+1 to standard form?

Answer this question

  • Convert 11-4x=(3x-2)^2+1 to standard form?


Answers

Answer #1 | 06/02 2014 20:38
11 - 4x = (3x - 2)² + 1 9x² - 12x + 4 + 1 + 4x - 11 = 0 9x² - 8x - 6 = 0 y = 9x² - 8x - 6 ¯¯¯¯¯¯¯¯¯¯¯¯¯  
Positive: 50 %
Answer #2 | 06/02 2014 20:24
9x^2 - 8x - 6 :)
Positive: 50 %
Answer #3 | 06/02 2014 20:28
step by step solution: http://symbolab.com/solver/equation-calculator/11-4x%3D(3x-2)%5E%7B2%7D%2B1 hope this helps
Positive: 50 %
Answer #4 | 06/02 2014 21:02
11 - 4x = (3x - 2)^2 + 1 9x^2 - 8x - 6 = 0
Positive: 50 %

Possible answer

Anonymous716505
Login to your account
Create new account